Debris transport over a sloped surface in tsunami-like flow conditions. Issue 2 (3rd April 2019) - Stolle, Jacob; Takabatake, Tomoyuki; Hamano, Go; Ishii, Hidenori; Iimura, Kotaro; Shibayama, Tomoya; Nistor, Ioan; Goseberg, Nils; Petriu, Emil
ABSTRACT: Debris loading has been identified during several forensic engineering field surveys in the aftermath of the 2004 Indian Ocean and 2011 Tohoku Japan tsunamis as a critical design load. However, little research has addressed the assessment of debris loading hazards. The study presented herein examines the entrainment and transport of debris over a 1:10 sloped bed as well as over a flat, horizontal bed in tsunami-like conditions. The study was performed at a 1:50 scale and the debris was modelled as scaled-down shipping containers. The friction between the debris and the bed was varied by modifying the material installed on the slope as well as by covering the surface of the debris surface with materials with different degrees of friction. The debris-bed friction influenced the characteristics of the initial entrainment of the debris, which varied from sliding to rolling, depending on the magnitude of the static friction. This study also determined that the friction did not have a significant effect on the lateral spreading of the debris. However, a significant difference was observed in the case of the longitudinal displacement of debris (in the flow direction).